Analisis Faktor-faktor yang Memengaruhi Pemilihan Sektor Pekerjaan Penduduk Pendatang Asal Luar Bali di Kota Denpasar - Fairuz Imarotul Wahyuni; Made Dwi Setyadhi Mustika (Public Service and Governance Journal, 2025)
Population movement or migration is a social process of the decision of each individual or group to move permanently or semi-permanently and settle in a desired area. The migration carried out certainly has various purposes, and one of the purposes of the population to migrate is to work. Bali is one of the regions in Indonesia that is in great demand and is used as a tourist destination by many people. However, its existence as a tourist destination area also makes Bali a target for migration destinations to get better jobs. The city of Denpasar as the capital of Bali Province also has a lot of potential cultural heritage destinations, in fact they are very concerned and develop cultural heritage sites in their city into a tour package, the many potentials of cultural heritage make the city of Denpasar then have a variety of jobs both in the formal and informal sectors. The objectives of this study are; 1) To analyze the influence of education level, age, working hours, income and work experience on the selection of employment sectors for immigrants from outside Bali in Denpasar City 2) To analyze the influence of education level, age, working hours, income and work experience partially on the selection of employment sectors for immigrants from outside Bali in Denpasar City and 3) To analyze the most dominant influence among education level, age, working hours, income and work experience on the selection of the employment sector of immigrants from outside Bali in the city of Denpasar. Using Binary Logistic Regression, the results of this study show that; 1) Education level, age, working hours, income, and work experience have a simultaneous effect on the selection of employment sectors for immigrants from outside Bali in Denpasar City 2) Education level and work experience partially have a positive effect on the selection of employment sectors. Meanwhile, age, income and working hours partially have a negative effect on the Selection of Job Sectors. 3) Income has the most dominant influence on the choice of job sector then followed by work experience, age, education and finally working hours.